GC-MS Analysis of Phytochemical Compounds in Aqueous Leaf Extract of Abrus Precatorius - Ibrahim, Wan Suriyani Wan; Ismail, Tuan Nadrah Naim Tuan; Salleh, Siti Farhanah Mohd; Ismail, Norzila (Penerbit Universiti Putra Malaysia, 2018)
Abrus precatorius is a flowering plant that belongs to the legume family, Fabaceae. In Malaysia, the leaves of Abrus precatorius are used traditionally to treat ailments such as fever, ulcer and mouth cancer. These traditional practices, however, have never been documented and usage of the plant is based on popular beliefs held by the local people. This work documented the phytocompounds that are present in the aqueous extract of Abrus precatorius leaves collected from a local area in Kota Bharu, Kelantan, Malaysia. The leaves were dried and then subjected to extraction using the decoction technique. The compounds were identified by gas chromatography with mass spectrometry analysis and characterised by comparison through the NIST02 and Wiley275 library search software. The GC-MS analysis showed that the classes of compounds identified in aqueous extracts of Abrus precatorius leaves were phenolic compounds, terpenoids and steroids